2008
DOI: 10.1002/dev.20294
|View full text |Cite
|
Sign up to set email alerts
|

Rats selectively bred for low levels of 50 kHz ultrasonic vocalizations exhibit alterations in early social motivation

Abstract: In rats, the rates of 50 kHz ultrasonic vocalizations (USVs) can be used as a selective breeding phenotype and variations in this phenotype can be an indicator of affective states. The 50 kHz USV is elicited by rewarding stimuli (e.g., food, sexual behavior) and therefore can express a positive affective state. Conversely, the 22 kHz USV is elicited by aversive stimuli (e.g., presence of a predator, social defeat) indicating a negative affective state. In the present study, we tested the effect of selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 57 publications
5
40
0
2
Order By: Relevance
“…Conversely, animals bred for low rates of 50-kHz USVs exhibited both lower rates of 50-kHz USVs as well elevated rates of 22-kHz USVs compared to randomly bred animals (Burgdorf et al, 2005;Harmon et al, 2008). These data suggest that high line animals exhibit a greater dispositional tendency for positive affectivity and a lower dispositional tendency for negative affectivity.…”
Section: Introductionmentioning
confidence: 43%
See 3 more Smart Citations
“…Conversely, animals bred for low rates of 50-kHz USVs exhibited both lower rates of 50-kHz USVs as well elevated rates of 22-kHz USVs compared to randomly bred animals (Burgdorf et al, 2005;Harmon et al, 2008). These data suggest that high line animals exhibit a greater dispositional tendency for positive affectivity and a lower dispositional tendency for negative affectivity.…”
Section: Introductionmentioning
confidence: 43%
“…In related work, low line animals failed to show a conditioned maternal preference (Harmon et al, 2008), using the procedures of Nelson and Panksepp (1996), whereas random and high line animals did show a maternal preference (Harmon et al, 2008). Therefore, it is possible that their lower social-motivation during adulthood reduces the likelihood of depressive responses (but their higher 22-kHz USVs would suggest increased susceptibility to depression).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS. Isolation-induced USVs are inherently social (Hofer et al, 2002;Harmon et al, 2008), and reductions of USVs have been found in rodent models of ASDs (Crawley, 2007;Higashida et al, 2011). Diminished USVs in rat pups are suggested to model the lack of crying observed in some children with ASDs (Crawley, 2007).…”
Section: Discussionmentioning
confidence: 99%